DEFINING AND CONSTRUCTING THE TEACHING MODEL OF ENTREPRENEUR EDUCATION BASED ON ENTREPRENEURIAL INTENTION MODEL - Henry Pribadi (Jurnal Teknik Industri: Jurnal Keilmuan dan Aplikasi Teknik Industri, 2005)
Concept of entrepreneurship has been widely debated whether to be an entrepreneur one need to get formal entrepreneurial education or not. Most of the formal entrepreneur education yield the same flaw, which is the lack of teaching soft skill and building the necessary entrepreneurship characteristics. Intention-based models of entrepreneurship education try to fill the gap by focusing the education on the human intention of becoming entrepreneur by defining four model of entrepreneurship education. An empirical research is conducted to show simple application on defining and understanding the model where the result could be used for giving some insight on constructing the appropriate model for entrepreneurship education in the future.